Porous carbon material as well as preparation method and application thereof

By employing a process of distillation to separate phenolic light fractions, ethylene urea-formaldehyde crosslinking, and Al-doped amino-grafted boron oxide nano-catalyzed carbonization, the problems of low raw material utilization and uneven pore size distribution in porous carbon materials were solved, resulting in the preparation of porous carbon materials with high conductivity and stability, suitable for sodium-ion batteries.

CN121247775AActive Publication Date: 2026-01-02SHIJIAZHUANG SHANGTAI TECH CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511803041.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-03
Publication Date
2026-01-02
Estimated Expiration
2045-12-03

AI Technical Summary

Technical Problem

Existing technologies for preparing porous carbon materials suffer from low raw material utilization and difficulty in achieving both high conductivity and pore size distribution that meets the requirements of CVD silicon deposition, resulting in unstable performance of silicon-carbon materials.

Method used

By separating light phenolic fractions through vacuum distillation, removing phenolic substances through alkaline solution extraction and weak acid regulation, and combining ethylene urea-formaldehyde crosslinking with Al-doped amino-grafted boron oxide nanocatalytic carbonization, the conductivity and pore size distribution of porous carbon materials can be precisely controlled.

Benefits of technology

It achieves high conductivity and stability of porous carbon materials, adapts to the electron transport efficiency and spatial structure of sodium-ion batteries, and enhances the utilization value of coal tar.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The invention relates to the technical field of carbon materials, and particularly discloses a porous carbon material and a preparation method and application thereof. Cheap and easily available coal tar is used as a raw material, phenol light fractions in the coal tar are directionally removed through reduced pressure distillation, heavy components are enriched, and then the enriched heavy components are sequentially subjected to processes such as pre-oxidation, formaldehyde-ethylene urea crosslinking, Al-doped amino grafted nano boric oxide catalytic carbonization and CO2 gradient activation to obtain the porous carbon material. The porous carbon material has high conductivity, pore size distribution meeting CVD silicon deposition requirements and a stable carbon skeleton, the porous carbon material with excellent comprehensive performance is provided for the sodium ion battery, high-value utilization of the coal tar is achieved, and the market prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon materials technology, and in particular to a porous carbon material, its preparation method, and its applications. Background Technology

[0002] The coking industry generates a large amount of coal tar as a byproduct during production. This substance is rich in phenols, aromatics, and other high-value organic compounds, making it an excellent raw material for the preparation of functional carbon materials. However, current traditional utilization methods for coal tar are mostly concentrated in low-value-added areas such as direct combustion. This not only fails to fully realize its resource value but also generates pollutants during combustion, placing a serious burden on the environment. Therefore, developing high-value-added conversion pathways for coal tar has become a critical issue that the industry urgently needs to address.

[0003] In the fields of new energy and new materials, CVD (chemical vapor deposition) silicon-carbon materials are widely used in key components such as lithium-ion battery anodes due to their excellent electrochemical performance. Porous carbon materials, as the core precursors for preparing CVD silicon-carbon, directly determine the final quality of the CVD silicon-carbon material. To meet the requirements for CVD silicon-carbon preparation, porous carbon materials must possess high specific surface area, a reasonable hierarchical pore structure (especially suitable for the mesopore ratio in silicon deposition), and good electrical conductivity. This places stringent requirements on the preparation process of porous carbon materials. Currently, the industry mostly uses coal tar pitch as a raw material to prepare porous carbon materials for silicon-carbon deposition. Although this raw material is derived from coal tar and has certain resource advantages, existing preparation technologies still have many technical bottlenecks in practical applications, making it difficult to meet the performance requirements of CVD silicon-carbon for porous carbon materials. The specific shortcomings are as follows: Existing technologies often use broad distillation and cutting processes for the pretreatment of coal tar, such as mixing coal tar fractions above 360°C, resulting in insufficient enrichment of key active components, leading to low raw material utilization efficiency and resource waste; moreover, existing processes cannot simultaneously control the degree of graphitization and pore structure, making it difficult for products to meet the dual requirements of high conductivity and pore size distribution that meets the needs of CVD silicon deposition, thus affecting the performance stability of subsequent silicon-carbon materials.

[0004] Therefore, developing a method for preparing porous carbon materials for silicon-carbon from coal tar that is efficient, environmentally friendly, and has excellent performance is of great practical significance and industrial value. Summary of the Invention

[0005] To address the problems of low raw material utilization and the inability to simultaneously meet the dual requirements of high conductivity and pore size distribution for CVD silicon deposition in existing processes for preparing porous carbon materials using coal tar pitch as raw material, this invention provides a porous carbon material, its preparation method, and its applications. This invention achieves enrichment of the heavy components by directionally removing phenolic light fractions from coal tar through vacuum distillation. The enriched heavy components are then subjected to pre-oxidation, formaldehyde-vinyl urea crosslinking, Al-doped amino-grafted boron oxide nano-catalyzed carbonization, and CO2 gradient activation. This process not only achieves high-value utilization of coal tar but also enables precise control of the conductivity and pore size distribution of the porous carbon. The resulting porous carbon possesses both excellent electron transport efficiency and a spatial structure suitable for sodium-ion storage, showing broad application prospects in the field of sodium-ion batteries.

[0006] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: In a first aspect, the present invention provides a method for preparing porous carbon materials, comprising the following steps: S1, the raw coal tar is distilled and separated to obtain a light fraction containing phenols; an alkaline solution is added to the light fraction containing phenols for extraction to obtain an oil phase; the pH of the oil phase is adjusted to weakly acidic, washed with water, and dehydrated to obtain refined coal tar; S2, Air is introduced into the refined coal tar and the temperature is raised for pre-oxidation to obtain pre-oxidized refined coal tar; S3, at 230℃~270℃, ethylene urea and part of formaldehyde are added to the pre-oxidized refined coal tar, the temperature is raised to 320℃~380℃, the remaining formaldehyde is added, and the temperature is kept warm to carry out the cross-linking reaction to obtain cross-linked refined coal tar. S4, Al-doped amino-grafted nano boron oxide is added to the cross-linked refined coal tar, the temperature is raised to 350℃~450℃, carbonization is carried out under an inert atmosphere, and then pulverized to obtain the precursor. S5, the precursor is activated in stages under a CO2 atmosphere to obtain a porous carbon material.

[0007] Compared with the prior art, the method for preparing porous carbon materials provided by the present invention first separates and enriches the light fraction containing phenols in the raw coal tar through distillation and cutting, and then removes the phenolic substances in a targeted manner through alkaline solution extraction, weak acid pH adjustment, water washing and dehydration, so as to avoid the phenolic substances interfering with the subsequent crosslinking and carbonization reactions. Then, after pre-oxidation, the refined coal tar undergoes a staged crosslinking process using ethylene urea and formaldehyde. First, all ethylene urea and a portion of formaldehyde are added in a low-to-medium temperature range, allowing ethylene urea to preferentially react with the active sites in the pre-oxidized refined coal tar, constructing a uniform reaction framework. The formaldehyde then assists in the formation of short-chain crosslinks. Next, the temperature is raised to 320℃~380℃, and the remaining formaldehyde is added. At this temperature, the reactivity of the aromatic groups in the coal tar and formaldehyde is significantly enhanced, enabling deep crosslinking between aromatic compounds. Furthermore, ethylene urea prevents excessive polymerization of formaldehyde through steric hindrance, significantly improving the uniformity of crosslinking. This uniform crosslinking not only ensures uniform shrinkage of the carbon framework after carbonization but also facilitates the formation of a continuous graphitized carbon framework during subsequent carbonization, improving the conductivity and stress resistance of the porous carbon material.

[0008] Traditional catalysts have weak interfacial bonding with organic carbon sources and are prone to agglomeration during carbonization. This results in excessive graphitization of local areas due to high catalyst concentration, while other areas are dominated by amorphous carbon due to catalyst scarcity, leading to uneven conductivity of porous carbon. The amino groups in Al-doped amino-grafted boron oxide nanoparticles can chemically bond with active groups (such as hydroxyl and carboxyl groups) in cross-linked coal tar, achieving uniform dispersion of the catalyst within the cross-linked coal tar matrix. This ensures consistent graphitization reaction rates and degrees in each region, resulting in a continuous network distribution of the final porous carbon graphitized regions without significant local over- or under-expansion. The electron transport pathways are coherent, significantly improving conductivity and stability. Furthermore, the uniform dispersion of Al-doped amino-grafted boron oxide nanoparticles in the cross-linked coal tar creates spatial barrier points. During subsequent carbonization, when the carbon source undergoes pyrolysis and shrinkage, the boron oxide nanoparticles hinder excessive shrinkage of the surrounding carbon matrix, forming channels of a certain size around the particles and directionally regulating the initial channel size range. Simultaneously, the interfacial bonding between the amino groups and the carbon source constrains the shrinkage direction of the carbon matrix during carbonization through interfacial forces, thus facilitating the formation of a regularly shaped pore structure. This initial hierarchical pore structure, after subsequent staged activation with CO2, can further optimize the mesopore ratio and pore size distribution, enabling the prepared porous carbon material to precisely meet the requirements of CVD silicon deposition or sodium ion insertion / extraction.

[0009] Further, in S1, the raw coal tar is subjected to vacuum distillation to collect a light fraction containing phenols at 170℃~210℃.

[0010] Specifically, in S1, the distillation rate of the phenolic light fraction is 5 mL / min to 10 mL / min.

[0011] Further, in S1, the alkaline solution is a NaOH solution with a mass concentration of 15% to 30%.

[0012] Further, in S1, the mass ratio of the phenolic light fraction to the alkaline solution is 1:(0.6~1.0).

[0013] Furthermore, in S1, the temperature of the stirring extraction is 50℃~70℃, and the stirring extraction time is 1h~2h.

[0014] Furthermore, in S1, the weak acidity refers to pH=6~7.

[0015] Specifically, in S1, the pH is adjusted to 6-7 using a sulfuric acid solution with a mass concentration of 4%~6%, then washed with water until no sulfate ions are present in the wash, and then vacuum dehydrated under conditions of 70℃~90℃ and -0.09MPa~-0.095MPa.

[0016] Phenolic substances are easily volatilized at high temperatures, causing raw material loss. Furthermore, volatilized phenolic substances are prone to condensation in the low-temperature areas of equipment, forming coke-like deposits that can clog pipelines and disrupt continuous production. In addition, the high reactivity of the hydroxyl groups in free phenols can easily lead to localized overreactions during the crosslinking stage, forming hard and brittle crosslinked blocks, resulting in an uneven crosslinked network and an inability to construct a complete three-dimensional crosslinked structure. Moreover, phenolic substances often combine with small amounts of sulfur- and nitrogen-containing heterocyclic compounds (such as thiophene and pyridine), increasing the difficulty of subsequent impurity removal. At the same time, phenolic substances are themselves highly polar substances, and excessive presence can disrupt the polarity balance of the oil phase system, leading to uneven dispersion of crosslinking agents such as formaldehyde and ethylene urea in the oil phase, further exacerbating local differences in the crosslinking reaction, and ultimately affecting the structural uniformity of the porous carbon precursor.

[0017] Through the above steps of distillation and cutting, alkaline solution extraction, and acid-adjusting washing, phenolic substances in coal tar can be effectively separated, ensuring that the residual amount of phenolic substances in refined coal tar is ≤0.5%, thus avoiding their impact on subsequent cross-linking and carbonization reactions.

[0018] Furthermore, in S2, the air flow rate is 150L / min to 250L / min.

[0019] Furthermore, in S2, the pre-oxidation temperature is 150℃~250℃, and the pre-oxidation time is 1h~3h.

[0020] Furthermore, in S2, the heating rate of the pre-oxidation is 4℃ / min to 6℃ / min.

[0021] The optimized pre-oxidation reaction conditions allow the refined coal tar to undergo a full oxidation reaction, gradually generating active groups such as hydroxyl and carboxyl groups, providing sufficient reaction sites for the cross-linking stage and the binding with ethylene urea and formaldehyde.

[0022] Furthermore, in S3, the total amount of formaldehyde used is 5% to 10% of the mass of the pre-oxidized refined coal tar; the partial formaldehyde is 50% to 80% of the total amount used.

[0023] Specifically, in S3, the stirring speed is increased to 300 rpm to 400 rpm, and then the temperature is raised to 320°C to 380°C, and the remaining formaldehyde is added.

[0024] Furthermore, in S3, the ethylene urea is 30wt% to 50wt% of the total formaldehyde.

[0025] Furthermore, in S3, the cross-linking reaction takes 2 to 4 hours.

[0026] In traditional processes, unbound free formaldehyde tends to remain in the crosslinking products, decomposing into impurities such as CO and H2O during subsequent carbonization, thus damaging the pore structure. This invention utilizes a staged ethylene urea-formaldehyde crosslinking method, which improves both the crosslinking density and the uniformity of crosslinking. In the first stage, at 230℃~270℃, some formaldehyde and all ethylene urea are added simultaneously to avoid excessive formaldehyde concentration in the first stage, which could lead to local overreaction. Furthermore, the diamino group of ethylene urea has higher reactivity than formaldehyde, allowing it to preferentially react with the active groups in coal tar, achieving uniform occupation of active sites. Additionally, the amino group of ethylene urea can react with formaldehyde molecules, enabling uniform anchoring of formaldehyde at active sites and preventing local accumulation or diffusion, thus avoiding problems of excessive or insufficient cross-linking. In the second stage, when the remaining formaldehyde is added at high temperature, a uniform ethylene urea-formaldehyde-coal tar preliminary cross-linked network has already formed within the system. Therefore, the subsequently added formaldehyde can rapidly react with the active groups in coal tar and the ethylene urea-formaldehyde intermediate to construct a long-chain interwoven uniform three-dimensional cross-linked network, providing a structural basis for the construction of a stable carbon skeleton during subsequent carbonization.

[0027] Further, in S4, the preparation method of the Al-doped amino-grafted boron oxide nanoparticles includes the following steps: Step a: Disperse boron oxide nanoparticles in an alcohol solvent to obtain a boron oxide nanoparticle dispersion; An aminosilane coupling agent is added to an acidic alcohol aqueous solution to obtain an aminosilane coupling agent solution. Step b: Add the aminosilane coupling agent solution to the nano boron oxide dispersion, heat to 60℃~70℃, keep the temperature for 2h~3h, separate the solid and liquid, wash, and dry to obtain amino-grafted nano boron oxide; Step c: The amino-grafted nano boron oxide is added to an aluminum salt aqueous solution, impregnated, evaporated to dryness, and then calcined at 500℃~600℃ in air atmosphere and ball-milled to obtain the Al-doped amino-grafted nano boron oxide.

[0028] Al-doped boron oxide nanoparticles can lower the activation energy for the transformation of aromatic structures to graphite structures in cross-linked coal tar, enabling the graphitization reaction to be efficiently initiated in the low-temperature range of 350℃ to 450℃. Amino groups can react with active groups in cross-linked coal tar through chemical bonds, improving the compatibility between boron oxide nanoparticles and coal tar, thereby enhancing the uniformity of boron oxide nanoparticle dispersion in coal tar. Through the catalytic and confinement effects of Al-doped amino-grafted boron oxide nanoparticles, precise control of the degree of porous carbon graphitization is achieved, and a suitable pore structure is constructed, solving the bottleneck problem of the difficulty in simultaneously achieving graphitization and pore structure in traditional catalysts.

[0029] Further, in step a, the alcohol solvent is anhydrous ethanol; the volume-to-mass ratio of the alcohol solvent to nano-boron oxide is (100~400) mL: (5~20) g.

[0030] Further, in step a, the preparation of the acidic alcohol aqueous solution includes the following steps: mixing alcohol solvent and water in a volume ratio of (10~50):(1~8) evenly, adjusting the pH to 4~5, and obtaining an acidic alcoholic solution.

[0031] Specifically, in step a, after adding the aminosilane coupling agent to the acidic alcohol aqueous solution, the mixture is stirred at room temperature for 15 to 20 minutes to obtain an aminosilane coupling agent solution.

[0032] Furthermore, the mass ratio of the aminosilane coupling agent to nano-boron oxide is (0.15~1.0):(5~20).

[0033] Specifically, the aminosilane coupling agent is KH-550.

[0034] Further, in step b, the mass ratio of the amino-grafted nano-boron oxide to the solute in the aluminum salt aqueous solution is (5~20):(0.1~2).

[0035] Further, in step b, the aluminum salt aqueous solution is an aluminum nitrate solution, and the concentration of the aluminum salt aqueous solution is 0.002 g / mL to 0.04 g / mL.

[0036] Furthermore, in step b, the temperature is raised to 500℃~600℃ using a programmed temperature rise method, with a heating rate of 4℃ / min~6℃ / min.

[0037] Furthermore, in step b, the carbonization time is 1.5h to 2.5h.

[0038] Further, in step b, the ball milling speed is 200 rpm to 400 rpm, the ball-to-material ratio is (5 to 10):1, and the ball milling time is 20 min to 90 min.

[0039] Furthermore, in S4, the amount of Al-doped amino-grafted nano-boron oxide added is 1% to 3% of the mass of the cross-linked refined coal tar.

[0040] Furthermore, in S4, the carbonization time is 2h to 4h.

[0041] Further, in S5, the phased activation specifically includes the following steps: heating the precursor to 750℃~850℃ and holding it at that temperature for 2h~4h, then heating it to 900℃~950℃ and holding it at that temperature for 1h~1.5h to obtain porous carbon material.

[0042] Al-doped amino-grafted boron oxide nanoparticles can not only regulate the degree of graphitization during the carbonization process of carbon sources and improve the conductivity of porous carbon materials, but also construct a preliminary hierarchical pore structure suitable for subsequent activation during the carbonization process, providing core support for the preparation of porous carbon with high conductivity and reasonable pore size distribution.

[0043] It should be noted that the inert atmosphere in this invention is provided by an inert gas. The inert gas can be nitrogen, argon, helium, etc., which are conventional in the art.

[0044] Secondly, the present invention also provides a porous carbon material, which is prepared by the method for preparing porous carbon materials described in any of the above claims.

[0045] Thirdly, the present invention also provides a negative electrode comprising the aforementioned porous carbon material.

[0046] Fourthly, the present invention also provides the application of the above-mentioned porous carbon material or the above-mentioned cathode in the preparation of sodium-ion batteries.

[0047] Fifthly, the present invention also provides a sodium-ion battery, comprising the aforementioned porous carbon material or the aforementioned positive electrode.

[0048] In a sixth aspect, the present invention also provides a battery module including the sodium-ion battery described above.

[0049] This invention uses readily available and inexpensive coal tar as raw material. Phenolic light fractions are removed by vacuum distillation to enrich the heavy components. The enriched heavy components are then subjected to a series of processes including pre-oxidation, formaldehyde-vinylurea crosslinking, Al-doped amino-grafted boron oxide nano-catalyzed carbonization, and CO2 gradient activation to obtain a porous carbon material. This porous carbon material possesses high conductivity, a pore size distribution suitable for CVD silicon deposition, and a stable carbon framework, providing a high-performance porous carbon material for sodium-ion batteries. It also achieves high-value utilization of coal tar and has broad market prospects. Detailed Implementation

[0050] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0051] To better illustrate the present invention, further examples are provided below.

[0052] Example 1 This invention provides a method for preparing porous carbon materials, the specific steps of which are as follows: S1. The raw coal tar was subjected to vacuum distillation, and the fraction distilled at 170℃~210℃ was collected at a distillation rate of 5mL / min to obtain a light fraction containing phenols. A 15% NaOH solution was added to the obtained light fraction containing phenols, with the mass of the NaOH solution being 0.8 times the mass of the light fraction containing phenols. The mixture was stirred and extracted at 60℃ for 1h. After standing and separating the layers, the aqueous phase was separated. The remaining oil phase was neutralized with 5% sulfuric acid solution to pH=6.7, washed with water until no sulfate ions were present in the washing liquid, and dehydrated under vacuum at 80℃ and -0.09MPa to obtain refined coal tar. HPLC analysis showed that the residual phenols were ≤0.5% and the ash content was ≤0.3%. S2, the above refined coal tar is transferred into a stirred reactor, air is introduced at a flow rate of 200 L / min, the temperature is raised to 200℃ at a rate of 5℃ / min, and held for 2 hours to obtain pre-oxidized refined coal tar; S3, the pre-oxidized refined coal tar is heated to 250℃, 70% of the total amount of formaldehyde and all of the ethylene urea are added, then the stirring speed is controlled at 300 rpm, the temperature is raised to 350℃, the remaining formaldehyde is added, and the temperature is maintained for 3 hours to obtain cross-linked refined coal tar; wherein, the total amount of formaldehyde is 10% of the mass of the pre-oxidized refined coal tar, and the amount of ethylene urea is 40 wt% of the total amount of formaldehyde; S4. Add 2% by mass of Al-doped amino-grafted nano-B2O3 to the above cross-linked refined coal tar, heat to 400℃, introduce nitrogen gas at a flow rate of 100mL / min, keep warm for 3h, and pulverize to 100 mesh to obtain catalyst precursor. S5. The above catalyst precursor is placed in a tube furnace and heated to 800°C for 3 hours under nitrogen protection. Then it is heated to 920°C for 1 hour and cooled to obtain porous carbon material.

[0053] The preparation method of the above-mentioned Al-doped amino-grafted nano-B2O3 includes the following steps: Weigh 10g of nano B2O3 and place it in a three-necked flask. Add 200mL of anhydrous ethanol and sonicate for 30min to obtain nano B2O3 dispersion. Measure 30 mL of anhydrous ethanol and 5 mL of deionized water, adjust the pH to 4.5 with 37% hydrochloric acid, add 0.4 g of KH550, and stir magnetically for 15 min to obtain a KH550 solution. KH550 solution was slowly added dropwise to the nano B2O3 dispersion at a rate of 1 mL / min, while stirring (200 rpm) and reflux were started simultaneously. The temperature was raised to 65℃ and the reaction was maintained at this temperature for 2 h. After the reaction was completed, the mixture was centrifuged at 8000 rpm for 15 min, the supernatant was discarded, the precipitate was washed with anhydrous ethanol, and dried under vacuum at 80℃ for 4 h to obtain amino-grafted nano B2O3. Weigh out 1.7g of Al(NO3)3 Add 9H2O to 50mL of deionized water and stir magnetically until completely dissolved to obtain an aluminum nitrate solution. Add 10g of the above-prepared amino-grafted nano-B2O3 to the aluminum nitrate solution and stir at 300rpm for 1h. Then transfer to a rotary evaporator and evaporate to dryness at 50℃ and -0.08MPa. Place in a muffle furnace and heat to 550℃ at a rate of 5℃ / min under air atmosphere, hold for 2.5h, and cool naturally to room temperature. Transfer the powder to a planetary ball mill, add agate balls with a ball-to-material ratio of 8:1, and mill at 300rpm for 30min to obtain Al-doped amino-grafted nano-B2O3.

[0054] Example 2 This invention provides a method for preparing porous carbon materials, the specific steps of which are as follows: S1. The raw coal tar was subjected to vacuum distillation, and the fraction distilled at 170℃~210℃ was collected at a distillation rate of 10mL / min to obtain a light fraction containing phenols. A 23% NaOH solution was added to the obtained light fraction containing phenols, with the mass of the NaOH solution being 0.7 times the mass of the light fraction containing phenols. The mixture was stirred and extracted at 70℃ for 1h. After standing and separating the layers, the aqueous phase was separated. The remaining oil phase was neutralized with 5% sulfuric acid solution to pH=6.5, washed with water until no sulfate ions were present in the washing liquid, and dehydrated under vacuum at 80℃ and -0.09MPa to obtain refined coal tar. HPLC analysis showed that the residual phenols were ≤0.5% and the ash content was ≤0.3%. S2, the above refined coal tar is transferred into a stirred reactor, air is introduced at a flow rate of 150 L / min, the temperature is raised to 230℃ at a rate of 4℃ / min, and held for 1 hour to obtain pre-oxidized refined coal tar; S3, the pre-oxidized refined coal tar is heated to 230℃, 80% of the total amount of formaldehyde and all of the ethylene urea are added, then the stirring speed is controlled at 400 rpm, the temperature is raised to 320℃, the remaining formaldehyde is added, and the mixture is kept at this temperature for 2 hours to obtain cross-linked refined coal tar; wherein, the total amount of formaldehyde is 9% of the mass of the pre-oxidized refined coal tar, and the amount of ethylene urea is 30 wt% of the total amount of formaldehyde; S4. Add 1.5% by weight of Al-doped amino-grafted nano B2O3 to the above cross-linked refined coal tar, heat to 350℃, introduce nitrogen gas at a flow rate of 100mL / min, keep warm for 4h, and pulverize to 100 mesh to obtain catalyst precursor. S5. The above catalyst precursor is placed in a tube furnace and heated to 750°C for 4 hours under nitrogen protection. Then it is heated to 950°C for 1 hour and cooled to obtain porous carbon material.

[0055] The preparation method of the above-mentioned Al-doped amino-grafted nano-B2O3 includes the following steps: Weigh 5g of nano B2O3 and place it in a three-necked flask. Add 100mL of anhydrous ethanol and sonicate for 30min to obtain nano B2O3 dispersion. Measure 10 mL of anhydrous ethanol and 1 mL of deionized water, adjust the pH to 4.2 with 37% hydrochloric acid, add 0.15 g of KH550, and stir magnetically for 15 min to obtain a KH550 solution. KH550 solution was slowly added dropwise to the nano B2O3 dispersion at a rate of 1 mL / min, while stirring (200 rpm) and reflux were started simultaneously. The temperature was raised to 60 °C and the reaction was maintained at this temperature for 3 h. After the reaction was completed, the mixture was centrifuged at 8000 rpm for 15 min, the supernatant was discarded, the precipitate was washed with anhydrous ethanol, and dried under vacuum at 80 °C for 4 h to obtain amino-grafted nano B2O3. Weigh out 0.1g of Al(NO3)3 Add 9H2O to 50mL of deionized water and stir magnetically until completely dissolved to obtain an aluminum nitrate solution. Add 5g of the above-prepared amino-grafted nano-B2O3 to the aluminum nitrate solution and stir at 300rpm for 1h. Then transfer to a rotary evaporator and evaporate to dryness at 50℃ and -0.08MPa. Place in a muffle furnace and heat to 600℃ at a rate of 6℃ / min under air atmosphere, hold for 2h, and allow to cool naturally to room temperature. Transfer the powder to a planetary ball mill, add agate balls at a ball-to-material ratio of 5:1, and mill at 200rpm for 60min to obtain Al-doped amino-grafted nano-B2O3.

[0056] Example 3 This invention provides a method for preparing porous carbon materials, the specific steps of which are as follows: S1. The raw coal tar was subjected to vacuum distillation, and the fraction distilled at 170℃~210℃ was collected at a distillation rate of 6mL / min to obtain a light fraction containing phenols. An 18% NaOH solution was added to the obtained light fraction containing phenols, with the mass of the NaOH solution being 0.9 times the mass of the light fraction containing phenols. Extraction was carried out at 50℃ with stirring for 2 hours. After standing and separation, the aqueous phase was separated. The remaining oil phase was neutralized to pH=6.4 with 5% sulfuric acid solution, washed with water until no sulfate ions were present in the washing liquid, and dehydrated under vacuum at 80℃ and -0.09MPa to obtain refined coal tar. HPLC analysis showed that the residual phenolic substances were ≤0.5% and the ash content was ≤0.3%. S2, the above refined coal tar is transferred into a stirred reactor, air is introduced at a flow rate of 160 L / min, the temperature is raised to 180℃ at a rate of 6℃ / min, and held for 3 hours to obtain pre-oxidized refined coal tar; S3, the pre-oxidized refined coal tar is heated to 270℃, 50% of the total amount of formaldehyde and all of the ethylene urea are added, then the stirring speed is controlled at 200 rpm, the temperature is raised to 360℃, the remaining formaldehyde is added, and the temperature is maintained for 3 hours to obtain cross-linked refined coal tar; wherein, the total amount of formaldehyde is 8% of the mass of the pre-oxidized refined coal tar, and the amount of ethylene urea is 35 wt% of the total amount of formaldehyde; S4. Add 1% by mass of Al-doped amino-grafted nano-B2O3 to the above cross-linked refined coal tar, heat to 450℃, introduce nitrogen gas at a flow rate of 100mL / min, keep warm for 2h, and pulverize to 100 mesh to obtain catalyst precursor. S5. The above catalyst precursor is placed in a tube furnace and heated to 850°C for 2 hours under nitrogen protection. Then it is heated to 900°C for 1.5 hours and cooled to obtain porous carbon material.

[0057] The preparation method of the above-mentioned Al-doped amino-grafted nano-B2O3 includes the following steps: Weigh 20g of nano B2O3 and place it in a three-necked flask. Add 400mL of anhydrous ethanol and sonicate for 30min to obtain nano B2O3 dispersion. Measure 50 mL of anhydrous ethanol and 8 mL of deionized water, adjust the pH to 4.8 with 37% hydrochloric acid, add 1.0 g of KH550, and stir magnetically for 15 min to obtain a KH550 solution. KH550 solution was slowly added dropwise to the nano B2O3 dispersion at a rate of 1 mL / min, while stirring (200 rpm) and reflux were started simultaneously. The temperature was raised to 70 °C and the reaction was maintained at this temperature for 2 h. After the reaction was completed, the mixture was centrifuged at 8000 rpm for 15 min, the supernatant was discarded, the precipitate was washed with anhydrous ethanol, and dried under vacuum at 80 °C for 4 h to obtain amino-grafted nano B2O3. Weigh out 2g of Al(NO3)3 Add 9H2O to 50mL of deionized water and stir magnetically until completely dissolved to obtain an aluminum nitrate solution. Add 20g of the above-prepared amino-grafted nano-B2O3 to the aluminum nitrate solution and stir at 300rpm for 1h. Then transfer it to a rotary evaporator and evaporate it to dryness at 50℃ and -0.08MPa. Place it in a muffle furnace and heat it to 500℃ at a rate of 4℃ / min under air atmosphere. Hold it at this temperature for 3h and allow it to cool naturally to room temperature. Transfer the powder to a planetary ball mill, add agate balls with a ball-to-material ratio of 10:1, and mill at 400rpm for 40min to obtain Al-doped amino-grafted nano-B2O3.

[0058] Example 4 This invention provides a method for preparing porous carbon materials, the specific steps of which are as follows: S1. The raw coal tar was subjected to vacuum distillation, and the fraction distilled at 170℃~210℃ was collected at a distillation rate of 8 mL / min to obtain a light fraction containing phenols. A 25% NaOH solution was added to the obtained light fraction containing phenols, with the mass of the NaOH solution being 0.7 times the mass of the light fraction containing phenols. The mixture was stirred and extracted at 55℃ for 2 h. After standing and separating the layers, the aqueous phase was separated. The remaining oil phase was neutralized with 5% sulfuric acid solution to pH=6.0, washed with water until no sulfate ions were present in the washing liquid, and dehydrated under vacuum at 80℃ and -0.09 MPa to obtain refined coal tar. HPLC analysis showed that the residual phenols were ≤0.5% and the ash content was ≤0.3%. S2, the above refined coal tar is transferred into a stirred reactor, air is introduced at a flow rate of 220 L / min, the temperature is raised to 180℃ at a rate of 5℃ / min, and held for 2.5 h to obtain pre-oxidized refined coal tar; S3, the pre-oxidized refined coal tar is heated to 240℃, 60% of the total amount of formaldehyde and all of the ethylene urea are added, then the stirring speed is controlled at 280 rpm, the temperature is raised to 330℃, the remaining formaldehyde is added, and the temperature is maintained for 4 hours to obtain cross-linked refined coal tar; wherein, the total amount of formaldehyde is 5% of the mass of the pre-oxidized refined coal tar, and the ethylene urea is 45 wt% of the total amount of formaldehyde; S4. Add 3% by mass of Al-doped amino-grafted nano-B2O3 to the above cross-linked refined coal tar, heat to 380℃, introduce nitrogen gas at a flow rate of 100mL / min, keep warm for 4h, and pulverize to 100 mesh to obtain catalyst precursor. S5. The above catalyst precursor is placed in a tube furnace and heated to 780°C for 3 hours under nitrogen protection. Then it is heated to 910°C for 1 hour and cooled to obtain porous carbon material.

[0059] The preparation method of Al-doped amino-grafted nano-B2O3 is the same as in Example 1 and will not be repeated here.

[0060] Example 5 This invention provides a method for preparing porous carbon materials, the specific steps of which are as follows: S1. The raw coal tar was subjected to vacuum distillation, and the fraction distilled at 170℃~210℃ was collected at a distillation rate of 7mL / min to obtain a light fraction containing phenols. A 20% NaOH solution was added to the obtained light fraction containing phenols, with the mass of the NaOH solution being 1.0 times the mass of the light fraction containing phenols. The mixture was stirred and extracted at 65℃ for 1h. After standing and separating the layers, the aqueous phase was separated. The remaining oil phase was neutralized with 5% sulfuric acid solution to pH=6.8, washed with water until no sulfate ions were present in the washing liquid, and dehydrated under vacuum at 80℃ and -0.09MPa to obtain refined coal tar. HPLC analysis showed that the residual phenols were ≤0.5% and the ash content was ≤0.3%. S2, the above refined coal tar is transferred into a stirred reactor, air is introduced at a flow rate of 250 L / min, the temperature is raised to 250℃ at a rate of 6℃ / min, and held for 1 hour to obtain pre-oxidized refined coal tar; S3, the pre-oxidized refined coal tar is heated to 260℃, 65% of the total amount of formaldehyde and all of the ethylene urea are added, then the stirring speed is controlled at 250 rpm, the temperature is raised to 340℃, the remaining formaldehyde is added, and the mixture is kept at this temperature for 3 hours to obtain cross-linked refined coal tar; wherein, the total amount of formaldehyde is 6% of the mass of the pre-oxidized refined coal tar, and the amount of ethylene urea is 50 wt% of the total amount of formaldehyde; S4. Add 2.5% by weight of Al-doped amino-grafted nano-B2O3 to the above cross-linked refined coal tar, heat to 420℃, introduce nitrogen gas at a flow rate of 100mL / min, keep warm for 2h, and pulverize to 100 mesh to obtain catalyst precursor. S5. The above catalyst precursor is placed in a tube furnace and heated to 750℃~850℃ under nitrogen protection for 2h~4h. Then it is heated to 900℃~950℃ for 1h~1.5h and cooled to obtain porous carbon material.

[0061] The preparation method of Al-doped amino-grafted nano-B2O3 is the same as in Example 2 and will not be repeated here.

[0062] Example 6 This invention provides a method for preparing porous carbon materials, the specific steps of which are as follows: S1. The raw coal tar was subjected to vacuum distillation, and the fraction distilled at 170℃~210℃ was collected at a distillation rate of 9 mL / min to obtain a light fraction containing phenols. A 30% NaOH solution was added to the obtained light fraction containing phenols, with the mass of the NaOH solution being 0.6 times the mass of the light fraction containing phenols. The mixture was stirred and extracted at 50℃ for 1 h. After standing and separating the layers, the aqueous phase was separated. The remaining oil phase was neutralized with 5% sulfuric acid solution to pH=6.2, washed with water until no sulfate ions were present in the washing liquid, and dehydrated under vacuum at 80℃ and -0.09 MPa to obtain refined coal tar. HPLC analysis showed that the residual phenols were ≤0.5% and the ash content was ≤0.3%. S2, the above refined coal tar is transferred into a stirred reactor, air is introduced at a flow rate of 210 L / min, the temperature is raised to 150℃ at a rate of 4℃ / min, and held for 3 hours to obtain pre-oxidized refined coal tar; S3, the pre-oxidized refined coal tar is heated to 265℃, 75% of the total amount of formaldehyde and all of the ethylene urea are added, then the stirring speed is controlled at 300 rpm, the temperature is raised to 380℃, the remaining formaldehyde is added, and the temperature is maintained for 2 hours to obtain cross-linked refined coal tar; wherein, the total amount of formaldehyde is 7% of the mass of the pre-oxidized refined coal tar, and the amount of ethylene urea is 38 wt% of the total amount of formaldehyde; S4. Add 2.3% by weight of Al-doped amino-grafted nano-B2O3 to the above cross-linked refined coal tar, heat to 430℃, introduce nitrogen gas at a flow rate of 100mL / min, keep warm for 2h, and pulverize to 100 mesh to obtain catalyst precursor. S5. The above catalyst precursor is placed in a tube furnace and heated to 810°C for 3 hours under nitrogen protection. Then it is heated to 930°C for 1 hour and cooled to obtain porous carbon material.

[0063] The preparation method of Al-doped amino-grafted nano-B2O3 is the same as in Example 3 and will not be repeated here.

[0064] Comparative Example 1 This comparative example provides a method for preparing porous carbon materials. The only difference from Example 1 is that the Al-doped amino-grafted nano-B2O3 in S4 is replaced with an equal amount of Al-doped carboxyl-grafted nano-B2O3. The rest is exactly the same and will not be described again here.

[0065] The preparation method of the Al-doped carboxyl-grafted nano-B2O3 includes the following steps: Weigh 10g of nano B2O3 and place it in a three-necked flask. Add 200mL of anhydrous ethanol and sonicate for 30min to obtain nano B2O3 dispersion. Measure 30 mL of anhydrous ethanol and 5 mL of deionized water, adjust the pH to 5.5 with 37% hydrochloric acid, add 0.4 g of KH560, and stir magnetically for 15 min to obtain a KH560 solution. KH560 solution was slowly added dropwise to the nano B2O3 dispersion at a rate of 1 mL / min, while stirring (200 rpm) and reflux were started simultaneously. The temperature was raised to 75 °C and the reaction was maintained at this temperature for 2 h. After the reaction was completed, the mixture was centrifuged at 8000 rpm for 15 min, the supernatant was discarded, the precipitate was washed with anhydrous ethanol, and the mixture was dried under vacuum at 80 °C for 4 h to obtain carboxyl-grafted nano B2O3. Weigh out 1.7g of Al(NO3)3 Add 9H2O to 50mL of deionized water and stir magnetically until completely dissolved to obtain an aluminum nitrate solution. Add 10g of the carboxyl-grafted nano-B2O3 prepared above to the aluminum nitrate solution and stir at 300rpm for 1h. Then transfer it to a rotary evaporator and evaporate it to dryness at 50℃ and -0.08MPa. Place it in a muffle furnace and heat it to 550℃ at a rate of 5℃ / min under air atmosphere, hold it at that temperature for 2.5h, and allow it to cool naturally to room temperature. Transfer the powder to a planetary ball mill, add agate balls with a ball-to-material ratio of 8:1, and mill at 300rpm for 30min to obtain Al-doped carboxyl-grafted nano-B2O3.

[0066] Comparative Example 2 This comparative example provides a method for preparing porous carbon materials. The only difference from Example 1 is that the Al-doped amino-grafted nano-B2O3 in S4 is replaced with an equal amount of Al-doped thiol-grafted nano-B2O3. The rest is exactly the same and will not be described again here.

[0067] The preparation method of the Al-doped thiol-grafted nano-B2O3 includes the following steps: Weigh 10g of nano B2O3 and place it in a three-necked flask. Add 200mL of anhydrous ethanol and sonicate for 30min to obtain nano B2O3 dispersion. Measure 30 mL of anhydrous ethanol and 5 mL of deionized water, adjust the pH to 4.3 with 37% hydrochloric acid, add 0.4 g of KH590, and stir magnetically for 15 min to obtain a KH590 solution. KH590 solution was slowly added dropwise to the nano B2O3 dispersion at a rate of 1 mL / min, while stirring (200 rpm) and reflux were started simultaneously. The temperature was raised to 70 °C and the reaction was maintained at this temperature for 2 h. After the reaction was completed, the mixture was centrifuged at 8000 rpm for 15 min, the supernatant was discarded, the precipitate was washed with anhydrous ethanol, and the mixture was vacuum dried at 80 °C for 4 h to obtain thiol-grafted nano B2O3. Weigh out 1.7g of Al(NO3)3 Add 9H2O to 50mL of deionized water and stir magnetically until completely dissolved to obtain an aluminum nitrate solution. Add 10g of the above-prepared thiol-grafted nano-B2O3 to the aluminum nitrate solution and stir at 300rpm for 1h. Then transfer to a rotary evaporator and evaporate to dryness at 50℃ and -0.08MPa. Place in a muffle furnace and heat to 550℃ at a rate of 5℃ / min under air atmosphere, hold for 2.5h, and cool naturally to room temperature. Transfer the powder to a planetary ball mill, add agate balls with a ball-to-material ratio of 8:1, and mill at 300rpm for 30min to obtain Al-doped thiol-grafted nano-B2O3.

[0068] Comparative Example 3 This comparative example provides a method for preparing porous carbon materials. The only difference from Example 1 is that the air pre-oxidation step S2 is omitted, and the formaldehyde-vinyl urea composite crosslinking step in S3 is carried out directly. The rest is exactly the same and will not be described again here.

[0069] Comparative Example 4 This comparative example provides a method for preparing porous carbon materials. The only difference from Example 1 is that the formaldehyde in S3 is added all at once, and ethylene urea is not added. The rest is exactly the same and will not be described again here. The specific steps in S3 are as follows: S3, the above pre-oxidized refined coal tar is heated to 250°C, formaldehyde is added, and the temperature is maintained for 3 hours to obtain cross-linked refined coal tar; wherein, the amount of formaldehyde used is 10% of the mass of the pre-oxidized refined coal tar.

[0070] Comparative Example 5 This comparative example provides a method for preparing porous carbon materials. The only difference from Example 1 is that the Al-doped amino-grafted nano-B2O3 in S4 is replaced with an equal amount of nano-B2O3. The rest is exactly the same and will not be described again here.

[0071] Comparative Example 6 This comparative example provides a method for preparing porous carbon materials, which differs from Example 1 only in that S5 is replaced with a one-stage activation; the rest is identical. Specifically, S5 is as follows: S5. The above catalyst precursor is placed in a tube furnace, heated to 900°C under nitrogen protection and held for 4 hours for activation, then cooled to obtain porous carbon material.

[0072] Comparative Example 7 This comparative example provides a method for preparing porous carbon materials. The only difference from Example 1 is that the Al-doped amino-grafted nano-B2O3 in S4 is replaced with an equal amount of nano-Fe2O3. The rest is exactly the same and will not be described again here.

[0073] Comparative Example 8 This comparative example provides a method for preparing porous carbon materials. The only difference from Example 1 is that the Al-doped amino-grafted nano-B2O3 in S4 is replaced with an equal amount of Al-doped nano-B2O3. The rest is exactly the same and will not be described again here.

[0074] The preparation method of the Al-doped nano-B2O3 includes the following steps: Weigh out 1.7g of Al(NO3)3 Add 9H2O to 50mL of deionized water and stir magnetically until completely dissolved to obtain an aluminum nitrate solution. Add 10g of nano-B2O3 to the aluminum nitrate solution and stir at 300rpm for 1h. Then transfer to a rotary evaporator and evaporate to dryness at 50℃ and -0.08MPa. Place in a muffle furnace and heat to 550℃ at a rate of 5℃ / min under air atmosphere, hold for 2.5h, and cool naturally to room temperature. Transfer the powder to a planetary ball mill, add agate balls with a ball-to-material ratio of 8:1, and mill at 300rpm for 30min to obtain Al-doped nano-B2O3.

[0075] Comparative Example 9 This comparative example provides a method for preparing porous carbon materials. The only difference from Example 1 is that the Al-doped amino-grafted nano-B2O3 in S4 is replaced with an equal amount of amino-grafted nano-B2O3. The rest is exactly the same and will not be described again here.

[0076] Weigh 10g of nano B2O3 and place it in a three-necked flask. Add 200mL of anhydrous ethanol and sonicate for 30min to obtain nano B2O3 dispersion. Measure 30 mL of anhydrous ethanol and 5 mL of deionized water, adjust the pH to 4.5 with 37% hydrochloric acid, add 0.4 g of KH550, and stir magnetically for 15 min to obtain a KH550 solution. KH550 solution was slowly added dropwise to the nano B2O3 dispersion at a rate of 1 mL / min, while stirring (200 rpm) and reflux were started simultaneously. The temperature was raised to 65 °C and the reaction was maintained at this temperature for 2 h. After the reaction was completed, the mixture was centrifuged at 8000 rpm for 15 min, the supernatant was discarded, the precipitate was washed with anhydrous ethanol, and dried under vacuum at 80 °C for 4 h to obtain amino-grafted nano B2O3.

[0077] The specific surface area, pore volume, and pore size distribution of the porous carbon materials prepared in Examples 1 to 6 and Comparative Examples 1 to 9 were tested using a nitrogen adsorption / desorption tester (Micromeritics ASAP 2020), and the resistivity of the porous carbon materials was tested using an impedance analyzer. The results are shown in Table 1.

[0078] Table 1

[0079] The results show that the air pre-oxidation, Al-doped amino-grafted nano-B2O3 as a carbonization catalyst, staged ethylene urea-formaldehyde crosslinking, and staged activation in the embodiments of the present invention are key synergistic process combinations for achieving breakthroughs in the comprehensive performance of porous carbon materials, and none of them can be omitted. The method for preparing porous carbon materials provided by the present invention effectively solves the problem in existing technologies of simultaneously achieving high conductivity and pore size distribution that meets the requirements of CVD silicon deposition. It provides a high-quality carbon matrix for the preparation of high-performance silicon-carbon composite materials by CVD. Furthermore, this preparation method uses coal tar, an industrial byproduct, as raw material, realizing the high-value recycling of resources, and has important practical value for promoting the coordinated development of the new energy industry and the circular economy.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing porous carbon materials, characterized in that, Includes the following steps: S1, the raw coal tar is distilled and separated to obtain a light fraction containing phenols; an alkaline solution is added to the light fraction containing phenols for extraction to obtain an oil phase; the pH of the oil phase is adjusted to weakly acidic, washed with water, and dehydrated to obtain refined coal tar; S2, Air is introduced into the refined coal tar and the temperature is raised for pre-oxidation to obtain pre-oxidized refined coal tar; S3, at 230℃~270℃, ethylene urea and part of formaldehyde are added to the pre-oxidized refined coal tar, the temperature is raised to 320℃~380℃, the remaining formaldehyde is added, and the temperature is kept warm to carry out the cross-linking reaction to obtain cross-linked refined coal tar. S4, Al-doped amino-grafted nano boron oxide is added to the cross-linked refined coal tar, the temperature is raised to 350℃~450℃, carbonization is carried out under an inert atmosphere, and then pulverized to obtain the precursor. S5, the precursor is activated in stages under a CO2 atmosphere to obtain a porous carbon material.

2. The method for preparing porous carbon materials as described in claim 1, characterized in that, In S2, the air flow rate is 150 L / min to 250 L / min; and / or In S2, the pre-oxidation temperature is 150℃~250℃, and the pre-oxidation time is 1h~3h; and / or In S2, the heating rate of the pre-oxidation is 4℃ / min to 6℃ / min.

3. The method for preparing porous carbon materials as described in claim 1, characterized in that, In S3, the total amount of formaldehyde used is 5% to 10% of the mass of the pre-oxidized refined coal tar; the portion of formaldehyde used is 50% to 80% of the total amount; and / or In S3, the ethylene urea is 30wt%~50wt% of the total formaldehyde; and / or In S3, the cross-linking reaction takes 2 to 4 hours.

4. The method for preparing porous carbon materials as described in claim 1, characterized in that, In S4, the preparation method of the Al-doped amino-grafted boron oxide nanoparticles includes the following steps: Step a: Disperse boron oxide nanoparticles in an alcohol solvent to obtain a boron oxide nanoparticle dispersion; An aminosilane coupling agent is added to an acidic alcohol aqueous solution to obtain an aminosilane coupling agent solution. Step b: Add the aminosilane coupling agent solution to the nano boron oxide dispersion, heat to 60℃~70℃, keep the temperature for 2h~3h, separate the solid and liquid, wash, and dry to obtain amino-grafted nano boron oxide; Step c: The amino-grafted nano boron oxide is added to an aluminum salt aqueous solution, impregnated, evaporated to dryness, and then calcined at 500℃~600℃ in air atmosphere and ball-milled to obtain the Al-doped amino-grafted nano boron oxide.

5. The method for preparing porous carbon materials as described in claim 4, characterized in that, The mass ratio of the aminosilane coupling agent to nano-boron oxide is (0.15~1.0):(5~20); and / or The mass ratio of the amino-grafted nano-boron oxide to the solute in the aluminum salt aqueous solution is (5~20):(0.1~2).

6. The method for preparing porous carbon materials as described in claim 1, characterized in that, In S4, the amount of Al-doped amino-grafted nano-boron oxide added is 1% to 3% of the mass of the cross-linked refined coal tar; and / or In S4, the carbonization time is 2h~4h.

7. The method for preparing porous carbon materials as described in claim 1, characterized in that, In S5, the phased activation specifically includes the following steps: heating the precursor to 750℃~850℃ and holding it at that temperature for 2h~4h, then heating it to 900℃~950℃ and holding it at that temperature for 1h~1.5h to obtain porous carbon material.

8. A porous carbon material, characterized in that, It is prepared by the method for preparing porous carbon materials according to any one of claims 1 to 7.

9. A negative electrode, characterized in that, Including the porous carbon material as described in claim 8.

10. A sodium-ion battery, characterized in that, It includes the porous carbon material of claim 8 or the negative electrode of claim 9.

Citation Information

Patent Citations

  • Preparation method of coal tar-based nitrogen-doped porous carbon material, product thereof and application of product in super capacitor

    CN111960403A

  • Method for preparing carbon nanospheres based on medium and low temperature coal tar and carbon nanospheres

    CN115707651A

  • Coal tar-based nitrogen-sulfur co-doped porous carbon material and preparation method thereof

    CN120270991A

  • Coal tar-based capacitor carbon, and preparation method and application thereof

    CN120341050A

  • AU2020102823A4